2012
DOI: 10.1111/j.1740-0929.2012.01011.x
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives on improvement of reproduction in cattle during heat stress in a future Japan

Abstract: Heat stress (HS) causes hyperthermia, and at its most severe form, can lead to death. More commonly, HS reduces feed intake, milk yield, growth rate and reproductive function in many mammals and birds, including the important cattle breeds in Japan. Rectal temperatures greater than 39.0°C and respiration rates greater than 60/min indicate cows are undergoing HS sufficient to affect milk yield and fertility. HS compromises oocyte quality and embryonic development, reduces expression of estrus and changes secret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(45 citation statements)
references
References 63 publications
0
37
0
Order By: Relevance
“…; Kadokawa et al . ). Within 24 h, heat stress can play a negative effect on milk production and reproduction of Holstein cattle, which induces a rapid and acute reduction (Silanikove et al .…”
Section: Discussionmentioning
confidence: 97%
“…; Kadokawa et al . ). Within 24 h, heat stress can play a negative effect on milk production and reproduction of Holstein cattle, which induces a rapid and acute reduction (Silanikove et al .…”
Section: Discussionmentioning
confidence: 97%
“…Acclimation to thermal stress also imposes physiological and metabolic adjustments associated with reduction of performance (Ispierto et al, 2007). Collier et al (2006) and Kadokawa et al (2012) detected a decrease in plasma glucose level for dairy cows in winter.…”
Section: Introductionmentioning
confidence: 94%
“…In Florida, temperatures of 29.7°C and 31.4ºC have been linked to average rectal temperatures of 39°C (mild hyperthermia) and 39.5°C (hyperthermia), respectively (Dikmen and Hansen, 2009). Rectal temperatures greater than 39°C reflect an extent of heat stress that will affect milk production and fertility (Hansen and Arechiga, 1999;West, 2003;Kadokawa et al, 2012). A THI value below 68 units generally does not cause safety problems for healthy animals; under mild discomfort and discomfort conditions (68 ≤ THI ≤ 74) heat stress begins to first cause problems; and for a THI above 75 units animals can show noticeable decrease in performance (Bouraoui et al, 2002;Hahn et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Increasing airflow and wetting frequency has significant improvement of milk production due to evaporative heat loss from the skin of dairy animals (Hillman et al, 2001;Domingos et al, 2013). Rectal temperature and respiration rate more than 39.0°C and 60 per minute indicated that, the cows are under heat stress and drastically reduced milk production and fertility (Kadokawa et al, 2012). Productivity of cows is reduced in hot environment due to poor thermoregulatory mechanism and less feed intake and poor metabolism rate (Abdelatif and Alameen, 2012;Rhoads et al, 2013).…”
Section: Introductionmentioning
confidence: 99%